The effect of COVID-19 on the presentation of thyroid disease in children - McCowan, Rebecca; Wild, Edith; Lucas-Herald, Angela K.; McNeilly, Jane; Mason, Avril; Wong, Sze Choong; Ahmed, S. Faisal; Shaikh, M. Guftar (Frontiers in Endocrinology, 2022)
Introduction: Although studies suggest a potential link between COVID-19 and thyroid dysfunction in adults, there are insufficient data to confirm that association in children, and whether there is any effect on presentation to healthcare services. Aims: To identify whether presentations of thyroid dysfunction in children to a tertiary paediatric hospital changed as a result of the COVID-19 pandemic. Methods: A retrospective case note review was conducted of all children with abnormal thyroid function tests between 1st January 2016 and 31st December 2021 at a tertiary paediatric endocrine centre in the United Kingdom. Results: Overall, 244 children whose first presentation was within the timeframe of interest were included in this study, with a median age (range) of 11.5 (6.1, 16.8) years. Of these, 43 (18%) were hyperthyroid and 201 (82%) were hypothyroid. The greatest number of thyroid presentations occurred in 2021 (n=60, 25% of total over time period) and the fewest in 2020 (n=10, 4% of total over time period). Prior to this, the median (range) number of presentations per year was 34 (28, 39). There were no statistically significant differences in biochemistry, antibody status or other clinical characteristics between those who presented with hyperthyroidism prior to the pandemic or after. In those with hypothyroidism, baseline biochemistry was similar between the 2 groups, but the presence of other autoimmune conditions was greater pre-pandemic (17.2% vs 15.0%, p=0.03). In addition, patients were more likely to have transient thyroid dysfunction, which did not require treatment post-pandemic (70.0% vs 49.6%, p=0.0086). Conclusions: Although overall rates of presentation with thyroid dysfunction have not altered since the first wave of the COVID-19 pandemic, presentations with transient thyroid dysfunction, not requiring ongoing treatment have increased. Further research regarding the relationship between COVID-19 and thyroid function in children and young people, is needed.